2020
DOI: 10.3389/fncel.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

PTPσ Knockdown in Lampreys Impairs Reticulospinal Axon Regeneration and Neuronal Survival After Spinal Cord Injury

Abstract: Traumatic spinal cord injury (SCI) results in persistent functional deficits due to the lack of axon regeneration within the mammalian CNS. After SCI, chondroitin sulfate proteoglycans (CSPGs) inhibit axon regrowth via putative interactions with the LAR-family protein tyrosine phosphatases, PTPσ and LAR, localized on the injured axon tips. Unlike mammals, the sea lamprey, Petromyzon marinus, robustly recovers locomotion after complete spinal cord transection (TX). Behavioral recovery is accompanied by heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
(94 reference statements)
0
8
1
Order By: Relevance
“…Our group used antisense morpholinos (MOs) to knock down lamprey PTPσ in vivo and studied its direct effects on the axon regeneration and retrograde neuronal death after SCI. Unexpectedly, we found that PTPσ knockdown in lamprey reduced axon regeneration and neuronal survival beginning between 10 and 20 weeks after TX (Rodemer et al, 2020). Those results seem to be inconsistent with the putative role of PTPσ in mammalian axon regeneration (Lang et al, 2015), and with the correlation between PTPσ mRNA and post-TX retrograde apoptotic signaling seen even after ChABC treatment in current study.…”
Section: Role Of Ptpσ In Axon Regenerationcontrasting
confidence: 89%
See 1 more Smart Citation
“…Our group used antisense morpholinos (MOs) to knock down lamprey PTPσ in vivo and studied its direct effects on the axon regeneration and retrograde neuronal death after SCI. Unexpectedly, we found that PTPσ knockdown in lamprey reduced axon regeneration and neuronal survival beginning between 10 and 20 weeks after TX (Rodemer et al, 2020). Those results seem to be inconsistent with the putative role of PTPσ in mammalian axon regeneration (Lang et al, 2015), and with the correlation between PTPσ mRNA and post-TX retrograde apoptotic signaling seen even after ChABC treatment in current study.…”
Section: Role Of Ptpσ In Axon Regenerationcontrasting
confidence: 89%
“…Those results seem to be inconsistent with the putative role of PTPσ in mammalian axon regeneration ( Lang et al, 2015 ), and with the correlation between PTPσ mRNA and post-TX retrograde apoptotic signaling seen even after ChABC treatment in current study. In our previous report, the lack of activated caspases in RS neurons, and the long latency after PTPσ knockdown in vivo indicated that enhanced supraspinal neuronal death might result from non-apoptotic mechanisms: by incidentally transfected infiltrating immune cells, or trophic deprivation, or autonomous autophagic mechanisms ( Rodemer et al, 2020 ). It also is possible that the redundancy of CSPG receptors mitigated the beneficial effect of in vivo PTPσ knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…In lampreys, both LAR and PTPσ are expressed selectively in neurons that regenerate poorly post-axotomy (Zhang et al, 2014 ). Paradoxically, knockdown of PTPσ by retrograde delivery of morpholinos from the transection site was followed by inhibition of regeneration and reduction in some measures of locomotor recovery (Rodemer et al, 2020 ). Presumably, PTPσ plays more than one role in the nervous system and the net effect of its knockdown may depend on the balance among its several roles in a given species and environment.…”
Section: Several Transmembrane Receptors Mediate Growth Suppression Omentioning
confidence: 99%
“…We have found several CSPG receptors in the lamprey genomic database (Zhang et al, 2014a ; Rodemer et al, 2020 ), and previously cloned the full-length of two receptor protein tyrosine phosphatases (RPTPs) protein tyrosine phosphatase sigma (PTPσ) and leukocyte antigen-related protein tyrosine phosphatase (LAR). Using ISH, we found that these CSPG receptors are expressed selectively in poorly regenerating/poorly surviving reticulospinal (RS) neurons both in uninjured animals and after SCI (Zhang et al, 2014a ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that CSPGs and their receptors may play a role in both the poor intrinsic regenerative ability of some neurons and in their susceptibility to retrograde cell death. However, knockdown of the CSPG receptor PTPσ by morpholinos applied to the SC-TX impaired RS axon regeneration and neuronal survival after SCI (Rodemer et al, 2020 ). This result was inconsistent with the putative role of PTPσ in axon regeneration and neuronal survival after axotomy.…”
Section: Introductionmentioning
confidence: 99%